Enhancing EFL students’ reading proficiency and engagement through the KWL Strategy in descriptive texts - Susana, Shofa Alfia; Rojabi, Ahmad Ridho (Journal of English in Academic and Professional Communication, 2025)
Enhancing students' reading ability for understanding descriptive texts is a prevalent challenge when learning English. Many students struggle to fully engage with and comprehend the contents of the text. As a result, using the KWL (Know, Want, Learned) strategy could assist students in better understanding the text's main idea. This strategy aims to stimulate students' prior knowledge, guide the reading process, and organise ideas after reading. This study aims to explore whether the KWL strategy can improve students' understanding of descriptive texts while also fostering their engagement in reading class activities. The Classroom Action Research (CAR) method was used in two cycles: planning, action, observation, and reflection. Each cycle included two learning sessions and one reading test session. The study included 30 students, and data was gathered through tests, observations, and interviews. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed thematically. The results revealed that students' average scores increased from pre-test (42.16) to post-test 1 (60.5) and post-test 2 (67.83), indicating a significant improvement in reading skills. These findings also demonstrated that the KWL strategy encourages students to actively engage in the learning process, such as enthusiasm in completing the KWL columns and participating in class discussions. The pedagogical implication is that instructors may utilize this strategy to create more interactive learning experiences and help students more deeply comprehend descriptive texts.